Emerging business online : global markets and the power of B2B internet marketing - Fawzy, Lara , 1981-; Dworski, Lucas , 1980- (FT Press, 2011)
This book introduces "ebocube" (Emerging Business Online), a comprehensive, proven framework for Internet B2B marketing in emerging markets. Step by step, readers discover how to use ebocube to integrate all stages of marketing and sales, reduce risks, and more